Pro/con clinical debate: The use of a protected specimen brush in the diagnosis of ventilator associated pneumonia - Heyland, Daren (BioMed Central, 2002)
Although mechanical ventilation is instituted as a life-saving technique, it may lead to complications that can negatively impact on patients' morbidity and/or mortality. Ventilator associated pneumonia (VAP) is one such complication that is a common challenge to intensivists. Although most experts would agree that early 'appropriate' antibiotic use is essential in patients who develop VAP, the best diagnostic test to guide decision-making is far from clear. One diagnostic test that is capable of providing microbiological samples from the lower respiratory tree is invasive bronchoscopy with a protected specimen brush. Such a procedure has long been available to intensivists and is frequently employed in many intensive care units. However, this procedure has associated costs and potential complications, and its utility in VAP has been challenged. In this issue of Critical Care Forum, the two sides of this debate are brought forward with compelling arguments. The authors' arguments should fuel future trials.